A pilot study examining the effects of faculty incivility on nursing program satisfaction - Dana Todd; Dina Byers; Katy Garth (Wolters Kluwer Medknow Publications, 2016)
Uncivil behavior in the classroom threatens the teaching-learning process. Research to date has focused on nursing student incivility in academia with little research examining the faculty role associated with incivility. Due to the lack of research examining faculty incivility toward nursing students, additional research in this area is indicated. The purpose of this study was to examine the effects of faculty incivility on nursing students' satisfaction with their Bachelor of Science Nursing (BSN) nursing program in a rural Southeastern state. Quantitative data was collected via surveys. Research questions included: (1) What percentage of senior nursing students report experiencing faculty incivility? (2) What is the relationship between faculty incivility and nursing students' ratings of program satisfaction? (3) In what educational settings does perceived incivility toward nursing students occur? (4) How do nursing students respond to perceived faculty incivility? The results of this survey revealed that 35.3% of students had at least one nursing instructor that put them down or was condescending toward them during their educational experience. Furthermore, 20.7% reported that two or more faculty put them down or were condescending toward them. Collectively, the pilot study revealed that over half of the participants reported faculty behaving in a way that was perceived as uncivil. Incivility in the nursing profession has been an on-going problem. The high number (over half) of participating students reporting that they perceived that at least one nursing instructor had put them down or was condescending toward them during their educational experience raises additional concerns for the level of civility in nursing programs and the role modeling that is presented to students. It is imperative that nursing faculty and students interact professionally and establish effective communication patterns.